2017
DOI: 10.2172/1343525
|View full text |Cite
|
Sign up to set email alerts
|

Exemplary Design Envelope Specification for Standard Modular Hydropower Technology

Abstract: The authors would like to thank the many stakeholders with whom we have engaged to elicit feedback on the opportunities and challenges associated with developing and deploying standard modular hydropower technologies. Ongoing engagement with these technology innovators, commercial service/equipment providers, project developers, and environmental stewards has yielded insight into the myriad perspectives and experiences that shape the current hydropower landscape and inform standard modular hydropower research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 92 publications
0
25
0
Order By: Relevance
“…The standard modular hydropower (SMH) project contemplates a new approach to SHP development focused on the principles of early development adoption of standardization, modularity, and environmental compatibility. These principles-outlined in detail in prior works (Witt et al 2016;Smith et al 2016)-are hypothesized as enabling pathways towards a low-cost, low-impact hydropower growth strategy.…”
Section: Standard Modular Hydropower Backgroundmentioning
confidence: 99%
“…The standard modular hydropower (SMH) project contemplates a new approach to SHP development focused on the principles of early development adoption of standardization, modularity, and environmental compatibility. These principles-outlined in detail in prior works (Witt et al 2016;Smith et al 2016)-are hypothesized as enabling pathways towards a low-cost, low-impact hydropower growth strategy.…”
Section: Standard Modular Hydropower Backgroundmentioning
confidence: 99%
“…The simulation use cases are defined scenarios that can effectively be addressed with the use of a model or group of models. These scenarios are constructed based on input from stakeholder concerns and priorities and leverage the functional requirements, relationships, and constraints from the EDES (Witt et al 2017). The use cases, discussed in greater detail in Section 3, are established to address the decision, design, and trade-off optimization issues relevant to SMH.…”
Section: Capability Assessment Assumptions and Expectationsmentioning
confidence: 99%
“…In Witt et al (2017), various objectives and requirements are identified for SMH generation, passage, and foundation modules and help form an EDES for SMH technology designs. In conjunction with those designs, this report serves to identify the simulation and modeling capabilities needed to predict whether proposed designs meet the desired objectives and requirements.…”
Section: Smh Simulation Use Casesmentioning
confidence: 99%
See 2 more Smart Citations